Advances in Intelligent Systems 2014
DOI: 10.2495/intelsys130221
|View full text |Cite
|
Sign up to set email alerts
|

A study of data randomization on a computer based feature selection for diagnosing coronary artery disease

Abstract: The objective of this research is to investigate the randomization of data on a computer based feature selection for diagnosing coronary artery disease. The randomization on Cleveland dataset was conducted because the performance value is different for each experiment. Assuming the performance values have a Gaussian probability distribution is a solution to handle different performance value provided by the process of randomizing dataset. The final performance is taken from the mean value of all performance va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…When compared with the proposed system, Akrami et al [ 28 ] achieved better results, but the resulting performance was still as good as that of category classification. Similar to the work by Prabowo et al [ 29 ], improved results were obtained for sensitivity and F-measure when the process is done with randomize variable selection for every 10-fold and it is performed 10 times. When compared with the case when no variable selection is carried out, the performance of the propose system is still better in terms of sensitivity and F-measure.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…When compared with the proposed system, Akrami et al [ 28 ] achieved better results, but the resulting performance was still as good as that of category classification. Similar to the work by Prabowo et al [ 29 ], improved results were obtained for sensitivity and F-measure when the process is done with randomize variable selection for every 10-fold and it is performed 10 times. When compared with the case when no variable selection is carried out, the performance of the propose system is still better in terms of sensitivity and F-measure.…”
Section: Discussionsupporting
confidence: 55%
“…The t -test results showed that the best performance classification method was SMO. The same approach was also adopted by Prabowo et al [ 29 ]. The research also investigated the performance of the algorithm computational intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…The test results showed that the SMO gives better performance of the other algorithm. Other similar studies have also been conducted by [6]. This study is similar to that done before, by using the binary classification approach.…”
mentioning
confidence: 62%
“…It is different for OAA-ECOC-SVM and SVM there is some level of value 0. If we compare with SMO (SVM Optimization) with a binary classification approach made [4] and [6], SVM multiclass have more stable performance in any type or level of coronary heart disease. The downside of multiclass classification is only able to give a good performance in diagnosing healthy, and not good for the other type or level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation